2012
DOI: 10.5099/aj120300204
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scaled Diethylene Triamine Pent Acetic Acid (N-DTPA): Novel Anti-Wilson's Disease Cell Model

Abstract: Wilson's disease (WD) is an autosomal recessive disorder in which copper metabolism is impaired. In fact, copper accumulates in various organs and tissues can be seen and causes toxic effects in various tissues including liver, brain, kidneys and eyes. Sulfur amino acid is a metabolite of D-penicillamine and penicillamine and copper Chlator is a factor that causes urinary excretion of copper and WD therapeutic agent as well. The interesting thing about the neurological symptoms of Wilson's disease with penicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Because glucose receptor mediated endocytosis pathway is led to high cell uptake of DTPA without cell destruction. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because glucose receptor mediated endocytosis pathway is led to high cell uptake of DTPA without cell destruction. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Because glucose receptor mediated endocytosis pathway is led to high cell uptake of DTPA without cell destruction. [13] Surveys such as studies conducted by Schibli et al have shown that when glucose is linked to a molecule through C2 position, its affinity for cell surface receptor doesn't alter essentially. [25] So, DTPA-DG can be transported through glucose channels with similar manner as unconjugated glucose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations